Attitudes towards menstruation: what women want? An Italian National Survey. (2nd January 2023) - Bastianelli, Carlo; Grandi, Giovanni; Farris, Manuela; Brandolino, Gabriella; Paoni Saccone, Giulia; La Barbiera, Ilenia; Benagiano, Giuseppe
Abstract: Objective: Many women experience negative feelings during menstrual bleeding. Aim of the study was to evaluate the attitudes of Italian women towards menstrual bleeding, their desire to reduce its frequency and knowledge of the existence of methods capable of achieving such an objective. Methods: An internet-based anonymous questionnaire has been sent to women willing to fill it in through different social media (Instagram, WhatsApp, Facebook, Twitter). The survey evaluated, objective parameters such as number of pads, use of painkillers, duration of period and pain intensity. Judgement towards period and knowledge about methods to reduce frequency and amount of menstrual flow were analysed. Result: 1072 Women aged 18 − 40 years, answered the survey. The level of education of responders was high, with 61.7% having a university degree. 27.5% of respondents viewed positively the occurrence of a menstrual period. Ideal frequency of menstrual cycles was considered 3 months and the perfect duration was considered to be 3 days. Half of the respondents ignored the existence of methods to suppress menstruation or reduce its frequency. 52% of participants stated that they would not use a contraceptive method because they considered it not 'natural'. Conclusions: In our sample, in spite of the discomfort reported by half of the women interviewed, menstruation was considered positively by one fourth as because confirm their fertility. The majority of women did consider bleeding every month a healthy, but they preferred a three-monthly frequency. Knowledge of contraceptive methods capable of reducing the frequency of menstrual bleeding was scarce.